Studi Pengaruh Variasi Parameter Pemesinan Terhadap Kekasaran Permukaan Pin Track Link Baja AISI 1045 - Wilujeng, Auliana; Angriawan, Bayu; Anas Fikri, Mohammad (Indonesian Society of Applied Science, 2024)
The track link pin is an important part of the excavator undercarriage which often experiences wear due to continuous friction. Excessive load is often the cause of increased track link pin wear. Therefore, this research makes a replacement material for AISI 1045 steel excavator track link pins by varying the machining parameters using the Taguchi method. In this research, track link pins were made using a conventional lathe. The manufacturing process is carried out by varying nine combinations of machining parameters, namely cutting depth (a), cutting speed (Cs), and feed motion (f). Each parameter is organized into three factor levels. Determination of the variation values ​​of these parameters is carried out based on the maximum limit conditions of the machine and the specifications of the tools used. The research results show that there is an influence of machining parameters on surface roughness. The surface roughness of the original material of the track link pin is N9. Of the nine levels of machining parameter combinations, there is one combination that produces a surface roughness of N8 (NOT GOOD), so that 88.89% of this research is rated GOOD.